Seedling production of endangered species by the micropropagation: the case of Alstroemeria - Leite , Douglas Machado; Oliveira, Ana Flávia de; Mendes , Fabíola Magalhães; Silva, Ana Lídia dos Santos; Tonetti, Olivia Alvina Oliveira; Brondani, Gilvano Ebling (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2025)
Campos Rupestres Ferruginosos” present specific environmental conditions and plant species in their composition considered to be in danger of extinction. Alstroemeria plantaginea Mart. ex Schult. & Schult.f. is an endemic species that occurs in areas of rocky outcrops. This study aimed to develop a protocol for the in vitro germination and micropropagation of Alstroemeria plantaginea, aiming at its conservation and production. Seeds were subjected to an aseptic treatment with NaOCl and two temperatures were tested to germination. In the multiplication and elongation, two forms of shoot production were used: individualized stems and shoot clusters, testing BAP concentrations and light quality. In rooting, glucose and sucrose were tested, and acclimatization was performed according to the rooting carbohydrate source. Germination only occurred under alternating temperatures (20-30°C). In the multiplication, the 0.5 mg L⁻¹ of BAP and the blue light quality favored the obtaining of buds and the emergence of leaves, with the cluster explant being the most observed. Carbohydrate sources did not show significant difference in rooting, however, the plants rooted in sucrose showed greater survival in acclimatization. In the end, it was possible to develop an in vitro germination and micropropagation protocol aiming at the conservation of the species and obtaining seedlings in 150 days. Index terms: Campo Rupestre Ferruginoso, in vitro cultivation, Canga ecosystem, light spectrum quality.